Decreased Sex Hormone-Binding Globulin Indicated Worse Biometric, Lipid, Liver, and Renal Function Parameters in Women with Polycystic Ovary Syndrome - Xi Luo; Xin-Ming Yang; Wang-Yu Cai; Hui Chang; Hong-Li Ma; Yan Peng; Xiao-Ke Wu (International Journal of Endocrinology)
Objective. To investigate the relationships between sex hormone-binding globulin (SHBG) and comprehensive metabolic parameters including biometric, glycemic, lipid, liver, and renal functions of women with polycystic ovary syndrome (PCOS). Study Design and Methods. A total of 1000 women diagnosed as PCOS by modified Rotterdam criteria were enrolled in a randomized controlled trial. SHBG and comprehensive metabolic parameters were measured at the baseline visit. Metabolic parameters included biometric parameters, glucose and lipid panels, and liver and renal function parameters. An independent t-test and linear regression were performed to investigate the associations between SHBG and metabolic parameters. Logistic regression was used to detect the relationship between SHBG and the presence of metabolic syndrome. Results. In comparative analyses, PCOS women with lower SHBG levels had higher body mass index, waist circumference, insulin, homeostatic model assessment-insulin resistance (HOMA-IR) index, systolic and diastolic blood pressure, triglycerides, apolipoprotein B (APOB), low-density lipoprotein (LDL), aspartate transferase (AST), alanine transferase (ALT), and blood urea nitrogen (BUN), but lower high-density lipoprotein (HDL) and apolipoprotein A1 (APOA1). In linear regression, SHBG was inversely associated with waist circumference, systolic blood pressure, triglyceride, LDL, APOB, ALT, AST, and BUN but positively associated with HDL and APOA1 after adjusting the BMI. In logistic regression, SHBG is a protective predictor for metabolic syndrome (odds ratio = 0.96; 95% confidence interval: 0.95–0.97). The area under the receiver-operator characteristic curve is 0.732 with a 95% confidence interval of 0.695–0.770. SHBG <26.75 mmol/L is the cutoff point with the best Youden index, which has a sensitivity of 0.656 and specificity of 0.698. Conclusions. Lower SHBG was associated with worsening biometric, lipid, liver, and renal functions but not glycemic parameters among women with PCOS. SHBG can be used as a tool to screen metabolic syndrome. This trial is registered with NCT01573858 and ChiCTR-TRC-12002081.